Barriers to English language development: Effort, learning attitudes, and artificial intelligence - Nur Aisyah; Nurhalizah Zain; Siti Nurul Alfiah; Miftahulfadlik Dabamona (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2025)
This study aims to examine the barriers to English learning related to learning efforts, learning attitudes, and artificial intelligence (AI) dependence on students of the English Language Education Study Program at IAIN Sorong. Despite the growing use of digital technology and AI, students still face various obstacles in building consistency and independence in learning English. This study uses a qualitative approach with a structured interview method for students in semesters 1, 3, and 5, as well as one lecturer who serves as the Head of the English Education Study Program. The data was analyzed using thematic analysis to identify the forms of obstacles experienced by students in the English language learning process. The results of the study showed that learning barriers varied between semester levels. 1st-semester students face obstacles in the form of low confidence, limited vocabulary, and high reliance on AI. 3rd-semester students experience obstacles in maintaining learning consistency and managing the use of AI effectively. Meanwhile, 5th-semester students face obstacles in the form of academic burden, time constraints, and increased reliance on AI, which has the potential to reduce independent learning efforts. Although students show a relatively positive attitude towards learning English, these various obstacles affect the effectiveness and sustainability of the learning process. These findings show that the use of AI in English learning needs to be managed wisely so as not to strengthen learning barriers but rather to support the development of students' independence and language competence. Keywords: Learning barriers; AI dependency; English language learning; Learning attitudes; Learning efforts